2019
DOI: 10.15171/ipp.2019.09
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of different statins in rheumatoid arthritis; a randomized double-blind controlled clinical trial

Abstract: Introduction: Statin family drugs are lipid-lowering agents with anti-inflammatory effects. Objectives: The aim of our study was to evaluate anti-inflammatory effects of different statins in rheumatoid arthritis patients. Patients and Methods: Around 161 eligible subjects with rheumatoid arthritis were enrolled. They randomly were divided into three groups. The first group received 40 mg/daily atorvastatin, the second group received 40 mg/daily simvastatin, and the third group received placebo as control for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…After screening, 19 studies were finally included, and the basic information is shown in Table 1. In these included articles published between 2004 and 2020, a total of 22,906 patients were enrolled, with 14 studies using atorvastatin at doses ranging from 10 to 80 mg qd, [22][23][24][25][26][27][28][29][30][31][32][33][34][35] 2 studies using simvastatin at doses ranging from 5 to 10 mg qd, [36,37] and 3 studies using rosuvastatin at a dose of 20 mg qd. [38][39][40] The duration of therapy ranged from 8 weeks to 12 years and most of the subjects were women.…”
Section: Basic Characteristics and Study Qualitymentioning
confidence: 99%
“…After screening, 19 studies were finally included, and the basic information is shown in Table 1. In these included articles published between 2004 and 2020, a total of 22,906 patients were enrolled, with 14 studies using atorvastatin at doses ranging from 10 to 80 mg qd, [22][23][24][25][26][27][28][29][30][31][32][33][34][35] 2 studies using simvastatin at doses ranging from 5 to 10 mg qd, [36,37] and 3 studies using rosuvastatin at a dose of 20 mg qd. [38][39][40] The duration of therapy ranged from 8 weeks to 12 years and most of the subjects were women.…”
Section: Basic Characteristics and Study Qualitymentioning
confidence: 99%
“…The ESR and lipid profile of patients were measured before, and at the end of month three and month six. Both statins effectively improved disease activity, reflected by a reduced DAS-28 score and also improved LDL-c levels (Karimifar et al, 2019). Kitas et al evaluated the efficacy of atorvastatin for preventing cardiovascular complications in RA patients.…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%